Review: Biodiversity of forests over limestone in Southeast Asia with emphasis on the Philippines - Paul John Tolentino; JOHN RYAN L. NAVIDAD; MARJORIE DELOS ANGELES; DESAMARIE ANTONETTE P. FERNANDEZ; ELAINE LOREEN C. VILLANUEVA; REN DIVIEN R. OBEÑA; INOCENCIO E. BUOT, JR. (Society for Indonesian Biodiversity, 2020)
Abstract. Tolentino PJS, Navidad JRL, Angeles MD, Fernandez AP, Villanueva ELC, Obena RDR, Buot Jr IE. 2020. Review: Biodiversity of forests over limestone in Southeast Asia with emphasis on the Philippines. Biodiversitas 21: 1597-1613. A comprehensive review of literature was carried out to determine the status of plant and animal diversity on forests over limestone in Southeast Asia (SEA), particularly in the Philippines. Angiosperm records are available in Peninsular Malaysia (1216 spp.); West Java and Seram Indonesia (101 and 149 spp., respectively); Laos (135 spp.); Thailand and Myanmar (1 sp.); and Limestone areas in Vietnam. Pteridophytes were recorded in Malaysia (32 spp.) while Bryophytes are recorded in Peninsular Malaysia (59 spp.). In the Philippines, there are plant records in: Masbate (61 spp.); Isabela (169 spp. Pteridophytes); Bohol (12 spp.), and Samar forests over limestone (29 spp. palms and 20 spp. orchids). A floral assessment in Samar Island Natural Park (SINP) includes species (212 spp.) that can possibly be found but are not limited to karsts. New Philippine endemic species are also recorded in Cebu, Palawan, and Panay Island. There are animal records in SEA including Vietnam (Bats-36, Bird-1, and Langurs-5 spp.); Malaysia (Sciuridae-1, Bats-28, Birds-129, Reptiles-17, and Invertebrates-74 spp.); Thailand (Murids-12, Reptiles-11, and Amphibian-1 sp.); and Myanmar (Reptiles-15 spp.). Records in the Philippines include: Mammals (Bicol-9, Mt. Irid-24, Mt. Aruyan-1, and Cebu-1 species), and; Birds (Cebu-1 sp.). A terrestrial faunal assessment in SINP includes species (182 spp.) that can possibly be found but are not limited to karsts. Forests over limestone are still largely understudied and the potential of discovering species is high. Further research is critical to establish science-based initiatives and policies that will protect and conserve limestone ecosystem biodiversity while allowing the utilization of its biological resources at a sustainable level.